Structures and patterns of information flow among Chinese-language Library and Information Science journals - Chen, Ya-Ning (Malaysian Journal of Library and Information Science, 2018)
This study aimed to examine the hidden structures and patterns of information flow in Chinese-language Library and Information Science (LIS) journals in Taiwan. Thirteen Chinese LIS journals and 2,914 articles published between 2001 and 2012 were selected as subject and an aggregated 13x13 matrix was generated to perform journal-to-journal citation analysis. The twelve-year period was further divided into three individual periods of four years each to conduct journal-to-journal citation analysis for evolutional comparison. Social network analysis was used to discover the implicit structures and patterns embedded in Chinese-language LIS journals in Taiwan in terms of network structure. The embedded structures and patterns in the Chinese-language LIS journal network were characterized by Bonich’s Eigenvector degree centrality, Stephenson and Zelen’s information centrality and Freeman’s betweenness centrality. These were used to measure journal prominence and role, bottom-up clique to find core journals, and structural equivalence to show alternative publication outlets. The limitations of this study and future research directions are also discussed.